Launching the right career - Kate Wendleton (Thomson/Delmar Learning, 2006)
Launching the Right Career is full of exercises and assessment techniques to help you figure out which career is best for you. It s the same approach The Five O Clock Club has used for decades with professionals, managers, and executives. This book is also great for every college student and recent grad concerned about the future, and aware of the tight job market they are entering